Clay content modulates differences in bacterial community structure in soil aggregates of different size - Biesgen, Danh; Frindte, Katharina; Maarastawi, Sarah; Knief, Claudia (Geoderma, 2020)
•Limited impact of aggregate size on the soil bacterial community at field scale.•Microbial differences between aggregate size fractions increase with higher clay contents.•Small microaggregates (< 20 µm) host the most distinct microbiota.•Occluded small microaggregates host more oligotrophic bacteria than other aggregates. Aggregation of soil components is contributing to the formation of diverse habitats for microbial life. Soil aggregates of different size are known to promote niche differentiation. Moreover, aggregates differ in physical and chemical properties, therewith likely supporting biological diversity in soil. To evaluate whether different types of aggregates affect bacterial colonization, we analyzed the impact of aggregate size in dependence of soil clay content on the bacterial community composition. A further distinction was made between microaggregates that occur as free structures in the soil matrix and those that exist occluded within macroaggregates. Upon size fractionation of soil samples from a clay catena (19 – 34%), we analyzed the bacterial community composition in ten different aggregate fractions by amplicon sequencing of the 16S rRNA gene. Both the aggregate size and the clay content showed an influence on the bacterial community composition, although this influence explained only a minor amount of the total observed variation across all samples (approx. 10% each). The increasing clay content led to more distinct communities in aggregates of different size, especially the smallest microaggregate fractions (< 20 µm) became more distinct. This is explained by enhanced aggregate stability in soils of increasing clay content, resulting in the development of more distinct bacterial communities over time. Indicator species analysis revealed a preferential enrichment of copiotrophic bacteria in free microaggregates, while oligotrophic bacteria were enriched in occluded microaggregates, indicating that a further differentiation of the bacterial community occurs within this specific aggregate size fraction in dependence on the localization of the microaggregates in the soil matrix, being possibly related to differences in organic carbon quality. These findings show that further aggregate traits besides size, i.e. stability mediated by soil clay content and localization in the soil matrix, contribute to the diversification of bacterial communities in soil.